The Effect of the Time Token Cooperative Learning Model on Fifth-Grade Elementary Students' Learning Outcomes - Sidauruk, Rachel Monica; Silaban, Patri Janson; Raja, Bogor Lumban; Sipayung, Regina Fredrika; Gaol, Rumiris Lumban (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper discusses the use of the Time Token learning model for students’ learning outcomes in class V at SD Negeri 060938 Medan Johor in the academic year 2022/2023. Quantitative research methods are used in this study. The research population is 30 fifth-grade students at SD Negeri 060938 Medan Johor. The sampling is probability sampling samples for 30 students. The research result indicates that students’ students’ learning outcomes using the Time Token model are in the very good category with an average score of 80.3. The result of a correlation coefficient is 0.701, which means that if rcount 0.701 ≥ rtable 0.361, Ha is accepted. Hence, there is a significant effect of the Time Token learning model on students’ learning outcomes in class V at SD Negeri 060938 Medan Johor. It can also be seen from the results of the t-test, tcount 5.196 ≥ ttable 1.701 means Ha is accepted. In conclusion, there is a significant positive effect from the use of the Time Token learning model on students’ learning outcomes in class V at SD Negeri 060938 Medan Johor in the academic year 2022/2023.